2021
DOI: 10.3389/fimmu.2021.646681
|View full text |Cite
|
Sign up to set email alerts
|

Direct LC-MS/MS Analysis of Extra- and Intracellular Glycerophosphoinositol in Model Cancer Cell Lines

Abstract: Glycerophosphoinositols (GPIs) are water-soluble bioactive phospholipid derivatives of increasing interest as intracellular and paracrine mediators of eukaryotic cell functions. The most representative compound of the family is glycerophosphoinositol (GroPIns), an ubiquitous component of mammalian cells that participates in cell proliferation, cell survival and cell response to stimuli. Levels and activity of this compound vary among cell types and deciphering these functions requires accurate measurements in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Our results revealed that 1-(sn-glycero-3-phospho)-1D-myo-inositol had a high diagnostic value. 1-(sn-Glycero-3-phospho)-1D-myo-inositol, also known as glycerophosphoinositol, is produced through membrane phosphatidylinositol through two successive deacylation steps catalysed by phospholipase A2IVα 26 , 27 . According to a study, high glycerophosphoinositol levels indicate cellular phenomena associated with the activation of RAS/mitogen-activated protein kinase (MAPK) pathways 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that 1-(sn-glycero-3-phospho)-1D-myo-inositol had a high diagnostic value. 1-(sn-Glycero-3-phospho)-1D-myo-inositol, also known as glycerophosphoinositol, is produced through membrane phosphatidylinositol through two successive deacylation steps catalysed by phospholipase A2IVα 26 , 27 . According to a study, high glycerophosphoinositol levels indicate cellular phenomena associated with the activation of RAS/mitogen-activated protein kinase (MAPK) pathways 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The current mismatch of these m/z may be a reflection of the mechanistic differences in ionsation between MALDI and electrospray ionisation. Furthermore, it has been reported that triacylglycerides are difficult to detect with MALDI, while the water soluble glycerophosphoinositols poses problems for conventional chromatographic protocols in terms of resolution and reproducibility, and these species may not be triacylglycerides 28 , 32 . Further work could elucidate these putative lipid identities.…”
Section: Discussionmentioning
confidence: 99%
“…The lysoPC mainly comes from the circulation produced by PC via phospholipase A2. 20 , 21 Since the expression level of PC was significantly reduced, the byproduct of lysoPC would also decline. While comparing within the subregions of the samples, the expression of PC and choline was found to be significantly downregulated in the PL group (Figure 7 A).…”
Section: Discussionmentioning
confidence: 99%